Platinum-group elements (PGE) in the New Afton alkalic Cu-Au porphyry deposit, Canadian Cordillera, I: relationships between PGE, accessory metals and sulfur isotopes in pyrite - Boucher, Brandon M.; Robb, Samuel J.; Hanley, Jacob J.; Kerr, Mitchell J.; Mungall, James E. (Frontiers in Earth Science, 2023)
At the late Triassic New Afton alkalic porphyry Cu-Au deposit (British Columbia, Canada), pyrite is a widely distributed minor sulfide phase within hypogene ore where it predates Cu mineralization and hosts significant concentrations of Pd and Pt. Here we characterize pyrite major, minor and trace element composition by EPMA and LA-ICP-MS, and S isotopes (bulk pyrite and in situ SIMS in individual growth zones) to elucidate compositional variations at different stages of pyrite growth with respect to PGE deposition. At least two cycles of zoned Co-Ni-Pd-Pt-Se-As co-enrichment are recorded over two stages of pyrite growth at the New Afton deposit. Concentrations of Co (up to ~5.5 wt%; highest observed in any reported ore-forming system) and Ni (up to 1 wt%) overlap with pyrite from mafic-ultramafic platinum-group element (PGE) deposits, iron oxide±apatite and iron oxidecopper-gold deposits (IOA-IOCG), and mantle peridotite-associated base metal exhalative deposits. In early hypogene pyrite, high Pt (up to ~24 ppm) occurs in crystal cores that have high Co/Ni ratio (> ~7), high Co (> ~ 1 wt%) and are poor in Ni, Se, and As. With progressive growth, early hypogene pyrite rims and late hypogene cores record an initial Ni-Pd-As-Se (±Co) co-enrichment stage, followed by oscillations in composition (from "barren" to variably Co-Ni-Pd-Pt-As-Se-enriched). Pd in pyrite (up to ~70 ppm) is inversely correlated to Co/Ni ratio, being enriched when Co/Ni < ~7 and Ni > ~1000 ppm. The highest levels of Pd enrichment occur in the most Ni-and Se-enriched growth zones. The transition from early, high Co/Ni (Pt-enriched) to later, low Co/Ni (Pd-enriched) growth zones is accompanied by a decrease in pyrite δ 34 SVCDT of up to ~7‰ (4‰ range in single grains) with a total range in composition measured between -5.5 ‰ and +1.4 ‰. Subsequent to the shift to lower values, overgrowths of high Co/Ni pyrite formed with values of δ 34 SVCDT similar to the earliest Co-Pt-rich growth zones. Some combination of fluctuations in temperature and oxygen fugacity related to episodic cooling and hydrothermal recharge is required to explain the observed metal enrichment patterns and variations in S isotope values.